Gordon Ramsay : three-star chef. (London, United Kingdom : Quadrille Publishing Limited, 2007)
Gordon Ramsay's passion for good food and an eye for perfection that has consistently seen him receive three coveted Michelin stars. He has been called the best chef of his generation, and this book sees Gordon at his day job - running a three-star kitchen and producing food often described as 'sublime'. It shows 50 classic Gordon Ramsay recipes.
The 3-star experience -- The recipes -- Starters -- Main courses -- Desserts.
Includes index.
Keywords: COOKING